AN ANALYSIS OF CONSUMER INTENTION TO USE E-HAILING SERVICES AMONG GENERATION Z IN MALAYSIA - Aiman, Muhammad Syahmi; RASHID, UMI KARTINI (Research in Management of Technology and Business, 2023)
The advent of numerous mobile transportation applications has resulted in an increase in demand for e-hailing services, which has resulted in a significant transformation in the transportation sector in recent years. As a result, the goal of this research is to determine how attitudes, subjective norms, perceived behavioral control, and perceived usefulness relate to consumer intention among Malaysia's Generation Z. Additionally, by sending questionnaires to respondents among Generation Z, this study employs quantitative approaches. According to the Krejcie & Morgan sample size chart, this study should include 384 respondents. Data analysisis done using the statistical package for social science (SPSS). Descriptive analysis, Reliability Test, Normality Test, and Multiple Linear Regression Analysis make up the analysis. The outcome will demonstrate whether there is a relationship between attitude, subjective norm, perceived behavioral control, and perceived usefulness towards consumer intention to use e-hailing services among Generation Z in Malaysia. This report will contribute to academic research, e-hailing companies, and the Department of Transport Malaysia in terms of knowledge, demographic, and statistics of the e-hailing services